1945
DOI: 10.1021/ja01218a506
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Chromatography of the Methyl Glucoses1

Abstract: NotesVol. Ü7 duces a detectable amount of a volatile material giving the xanthate test for carbon disulfide. Mere oxygen concentration does not seem to govern the amount produced, for the test with air was very faint. The results also strongly suggest that ethylene alone is without effect.The poisoning effect of carbon disulfide on nickel catalysts is well known and may account for the erratic results obtained using Fieser's solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1946
1946
1955
1955

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The examination of adsorption columns, used for the separation of organic compounds, with ultraviolet light has become general practice. Norberg (84) and others showed that this technique could be used to separate quantitatively such closely related products as triand tetramethyl glucose. Kirchner (56) and others have carried out the separation of a number of acid mixtures whose p-phenyl phenacyl esters were adsorbed on silica gel and the characteristic fluorescence was observed.…”
Section: Fluorescence In Organic Analysismentioning
confidence: 99%
“…The examination of adsorption columns, used for the separation of organic compounds, with ultraviolet light has become general practice. Norberg (84) and others showed that this technique could be used to separate quantitatively such closely related products as triand tetramethyl glucose. Kirchner (56) and others have carried out the separation of a number of acid mixtures whose p-phenyl phenacyl esters were adsorbed on silica gel and the characteristic fluorescence was observed.…”
Section: Fluorescence In Organic Analysismentioning
confidence: 99%